2019
DOI: 10.1007/s00417-019-04521-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of Müller cell glucocorticoid signaling in diabetic retinopathy

Abstract: Diabetic Retinopathy (DR) is a sight-threatening complication associated with the highly prevalent diabetes disorder. Both the microvascular damage and neurodegeneration detected in the retina caused by chronic hyperglycemia have brought special attention to Müller cells, the major macroglia of the retina that are responsible for retinal homeostasis.Given the role of glucocorticoid signaling in anti-inflammatory responses and the almost exclusive expression of glucocorticoid receptors (GR) in retinal Müller ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…It is known that Müller cells are an important source of neurotrophic factors but also of pro-inflammatory and angiogenetic cytokines (Bringmann et al, 2009;Ruzafa et al, 2018;von Toerne et al, 2014;Hauck et al, 2007). They play an important role in DR pathogenesis (Subirada et al, 2018;Ghaseminejad et al, 2020) and it was also suggested that they are involved in retinal immune responses (Roberge et al, 1988;Rutar et al, 2015;Natoli et al, 2017;Lorenz et al, 2021a;Lorenz et al, 2021b). However, the impact of their protective or detrimental effects on retinal inflammation in DR and other neurodegenerative retinal diseases remains elusive so far.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that Müller cells are an important source of neurotrophic factors but also of pro-inflammatory and angiogenetic cytokines (Bringmann et al, 2009;Ruzafa et al, 2018;von Toerne et al, 2014;Hauck et al, 2007). They play an important role in DR pathogenesis (Subirada et al, 2018;Ghaseminejad et al, 2020) and it was also suggested that they are involved in retinal immune responses (Roberge et al, 1988;Rutar et al, 2015;Natoli et al, 2017;Lorenz et al, 2021a;Lorenz et al, 2021b). However, the impact of their protective or detrimental effects on retinal inflammation in DR and other neurodegenerative retinal diseases remains elusive so far.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, retinal Müller glial cells (RMG) have gained increasing attention, as they are involved in virtually every retinal disease and represent valuable therapeutic targets (reviewed in [1][2][3][4]). RMG are the principal macroglial cells of the retina [5] and span its entire thickness from the inner to the outer limiting membrane [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Müller cells dysfunction may further lead to an excess of glutamate, aggravating the neurotoxicity with neuron death [6,30,[36][37][38][39]. Another consequence of Müller dysfunction is represented by the downregulation of the K+ channel subtype Kir4.1 and aquaporins but not Kir2.1, leading to an anomalous potassium intake and swelling [30,31,40]. The Müller glia are induced under hypoxic condition or glucosedeprived to increase their production and secretion of vascular endothelium growth factor (VEGF), which is also further increased by the altered permeability [23,40,41].…”
Section: Neurovascular Unit Impairment In Diabetesmentioning
confidence: 99%